Burstone’s intrusion arch for deep overbite correction. Case report - Sánchez-Tito, Marco Antonio (2019)
Deep overbite is defined as a vertical malocclusion, where there is an increase of the overlap of the upper incisors over the lower incisors, it may be due to supraeruption of the anterior upper teeth, increase of the curve of Spee or a combination of both. We present a case of a 23 years old patient, with a convex profile, increased overbite and retroinclination of the central upper incisors. A Burstone´s intrusion arch was used for simultaneous correction of the supraeruption and retroinclination of the upper incisors, achiving a stable occlusion after two years of follow-up. This case allows to demonstrate the application of biomechanical concepts proposed by Burstone for the treatment of deep bite malocclusion.